LiVOPO4‐Modified Lithium‐Rich Layered Composite Cathodes for High‐Performance Lithium‐Ion Batteries. Issue 3 (4th January 2021) - Li, Tongxin; Li, Donglin; Zhang, Wei; Kong, Xiangze; Zhang, Peiqi; Ren, Xuqiang; Zhang, Qingbo; Gao, Jianhang; Fan, Xiaoyong; Gou, Lei
Abstract: Li‐rich layered oxide Li1.2 Ni0.13 Co0.13 Mn0.54 O2 (LNCMO) is a promising cathode material for high‐energy‐density lithium‐ion batteries (LIBs). However, it suffers from severe capacity fading and voltage decay, especially at high voltage (>4.5 V). In this study, we successfully design an active LiVOPO4 (LVOP) coating on the LNCMO surface. The LNCMO/LVOP composites exhibit enhanced rate capability and largely improved cycling stability during long‐term cycling. Such superior performances can be attributed to the active LVOP coating layer, which can suppress the parasitic reactions between the LNCMO surface and the electrolyte. This work shows the potential for designing Li‐rich layered composite cathode materials by coating the active phase for high energy/power LIBs. Abstract : Keep your coat on : An electrochemically active LiVOPO4 layer is successfully coated on the Li1.2 Ni0.13 Co0.13 Mn0.54 O2 surface. The Li1.2 Ni0.13 Co0.13 Mn0.54 O2 /LiVOPO4 composites exhibit a capacity retention of 69.3 % after 500 cycles, making it suitable for practical applications in high energy and high power lithium‐ion batteries.